Situation Report: Hungary, 28 April 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. In His Address to Karlovy Vary Conference, Kadar Announces Forthcoming Signing of Friendship and Mutual Assistance Treaty with GDR New Rules on Internal Trade to Better Safeguard Consumer Interests Site of Atomic Power Plant Selected Belgian Foreign Minister Arrives Hungaro-Iraqi Talks Concluded Delegation to Marianske Lazne - "Dialogue" between Marxists and Christians Soviet Economic Scholars Discuss New Economic Model in Budapest